2015
DOI: 10.1089/ees.2014.0283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methylisothiazolinone on Biological Treatment: Efficiency of SBRs and Bioindicative Studies

Abstract: HighlightsMIT has no effect on the efficiency of activated sludge to treat organic matter.Nitrification is severely affected by MIT, confirmed by FISH analysisRespirometric and bioindicative tests show acclimatization of heterotrophic species KeywordsMethylisothiazolinone; nitrification; activated sludge; bioindicative tests; SBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…2-Methyl-1,2-thiazol-3(2H)-one, also named methylisothiazolinone (MIT), and 1,2-Benzisothiazol-3(2H)-one, or benzisothiazolinone (BIT), are very common biocides employed in personal care products, detergents (Li et al, 2016a;Garcia-Hidalgo et al, 2016), roof and outdoor paints, paper materials, and in other important industrial applications (Jungnickel et al, 2008;Wieck et al, 2016, Wang et al, 2017Li et al, 2016b), i.e. in reverse osmosis processes for water reclamation and desalination (Li et al, 2016a) and, in high concentrations, in cooling towers, paper mills, and refinery industry (Amat et al, 2015). As a result, significant concentrations of MIT and BIT have been reported in wastewater treatment plants' (WWTPs') influent, effluent, and in surface water (Wieck et al, 2016;Speksnijder et al, 2010;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Methyl-1,2-thiazol-3(2H)-one, also named methylisothiazolinone (MIT), and 1,2-Benzisothiazol-3(2H)-one, or benzisothiazolinone (BIT), are very common biocides employed in personal care products, detergents (Li et al, 2016a;Garcia-Hidalgo et al, 2016), roof and outdoor paints, paper materials, and in other important industrial applications (Jungnickel et al, 2008;Wieck et al, 2016, Wang et al, 2017Li et al, 2016b), i.e. in reverse osmosis processes for water reclamation and desalination (Li et al, 2016a) and, in high concentrations, in cooling towers, paper mills, and refinery industry (Amat et al, 2015). As a result, significant concentrations of MIT and BIT have been reported in wastewater treatment plants' (WWTPs') influent, effluent, and in surface water (Wieck et al, 2016;Speksnijder et al, 2010;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…MIT was named allergen of the year IN 2013(Van Huizen et al, 2017. The biocidal effect of MIT also affects the efficiency of activated sludge in wastewater treatment and as a result, the efficiency of the nitrification process can decrease from 90 to 20 % (Amat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The energy and f osc of the initial conditions were calculated at the SA(3)-CASSCF(10,8)/cc-pV(D+d)Z level of theory. The previous (12,9) active space was reduced to (10,8) with the exclusion of the n orbital, as it did not significantly contribute to the description of the three lowest-lying excited states and their respective dynamics. Also, only three states were considered as these states are the most significant to the photodegradation of ISO.…”
Section: Non-adiabatic Dynamics Studymentioning
confidence: 99%
“…7 Unfortunately, due to their extensive usage, isothiazolinones have been detected in surface waters, household, and industrial wastewater, albeit in trace amounts, dating back to 2007. [9][10][11] Among these compounds, MIT is considered an emerging pollutant, 10 and isothiazolinones, in general, may pose a risk to aquatic ecosystems due to their robust biocidal properties. 9 Additionally, isothiazolinones are recognized to induce various adverse effects on human health and pose potential hazards in household and industrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…Nontarget prokaryotes may also be impaired. In wastewater‐treatment settings, Amat et al (2015) and Zeng et al (2020) both reported a negative impact of MIT shocks on nitrification activity, with a modified composition of bacterial community in activated sludge. Given the extensive range of potential effects and affected organisms, and the scarcity of available data, it is crucial to expand our knowledge about environmental concentrations of isothiazolinones and their concomitant toxicity to freshwater ecosystems (Kresmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%